Science on Women and Women in Science in the Dutch Republic - van Deinsen, Lieke; Hollewand, Karen (Early Modern Low Countries, 2025)
This article brings together the main historiographical discussions that concentrate on women in science and science on women in the early modern Low Countries, with a focus on recent decades and the Dutch Republic. Modern scholarship on the early modern Dutch scholars, writers, and thinkers that discussed the female nature in this period is relatively limited. The first part of the article brings together publications on seventeenth- and eighteenth-century developments in Dutch anatomy, studies that discuss the ideas of particular scholars, for example Johannes Swammerdam (1637-1680), Reinier de Graaf (1641-1673), and Frederik Ruysch (1638-1731), and the recent work on the early modern debate on female education. In contrast, current scholarship that discusses the role of women in scientific and scholarly debates in the Dutch Republic is a broad and varied field, consisting of studies on the genres in which the debate about the (potential) position of learned women was conducted, of in-depth explorations of the lives and works of individual women, and, more recently, of projects that construct a more collective understanding of female participation in the intellectual domain. Building on recent insights, this contribution makes a plea for interdisciplinarity and a more integral perspective that moves beyond the disciplinary, the singular, and the exceptional.